Industry and revolution : social and economic change in the Orizaba Valley, Mexico - Gómez Galvarriato, Aurora (Harvard historical studies, 2013)
Industrial workers, not just peasants, played an essential role in the Mexican Revolution. Tracing the introduction of mechanized industry into the Orizaba Valley, Aurora Gómez-Galvarriato argues convincingly that the revolution cannot be understood apart from the Industrial Revolution, and thus provides a fresh perspective on both transformations.